Discovery of an Ultra‐rapid and Sensitive Lysosomal Fluorescence Lipophagy Process - Zhang, Hong; Shi, Lei; Li, Kun; Liu, Xin; Won, Miae; Liu, Yan‐Zhao; Choe, Youmi; Liu, Xin‐Yao; Liu, Yan‐Hong; Chen, Shan‐Yong; Yu, Kang‐Kang; Kim, Jong Seung; et al. (Angewandte Chemie International Edition, 2022)
Non‐invasive dynamic tracking of lysosomes and their interactions with other organelles is important for the study of lysosomal function and related diseases. However, many fluorescent dyes developed so far to target lysosomes cannot be used to monitor these processes due to the high concentrations required for imaging, long cell penetration times, and non‐ideal photostability. In this regard, we synthesized three lysosomal targeting probes with large Stokes shifts, good stability, and high brightness. The Q‐P‐ARh dye, developed by us for the first time, can stain lysosomes at ultra‐low concentrations (1.0 nM) without affecting the physiological functions of the lysosomes. More importantly, its excellent anti‐interference ability and ultrafast lysosomal staining ability (within 1.0 min) clearly monitored the entire dynamic process of lipophagy. Ultimately, this method can greatly contribute to the study of autophagy pathways. This novel fluorescence platform shows great promise for the development of biological probes for application in pathological environments. A series of brand‐new large Stokes shift and highly stable fluorescent dyes were constructed. In particular, the Q‐P‐ARh fluorescent dye as a near‐infrared emission lysosomal‐specific probe with ultra‐low concentration and ultra‐fast staining characteristics for the complete lipophagy process imaging is presented.